Answer:
(x, y) = (8, -3)
Step-by-step explanation:
You can substitute for x in the first equation:
3(-3y -1) +3y = 15
-6y = 18 . . . . . add 3 and simplify
y = -3 . . . . . . . divide by -6
x = -3(-3) -1 = 8 . . . . find x using the second equation
The solution to this system of equations is (x, y) = (8, -3).
Answer:
A: 0
B: pi/3
E: 5pi/3
Step-by-step explanation:
The answer will end up being c
Answer:
![= 2\pi \: r \: h \\ 2 \times \pi \times 4 \times 9 \\ = 226 .19 {cm}^{2}](https://tex.z-dn.net/?f=%20%3D%202%5Cpi%20%5C%3A%20r%20%5C%3A%20h%20%5C%5C%202%20%5Ctimes%20%5Cpi%20%5Ctimes%204%20%5Ctimes%209%20%5C%5C%20%20%3D%20226%20.19%20%7Bcm%7D%5E%7B2%7D%20)
Can I have the brainliest please?
Answer:
Step-by-step explanation:
y²-y-4x=0
differentiate w.r.t. x
2y*y^1-y^1-4=0
(2y-1)y^1=4
y^1=4/(2y-1)